4D printing: Fundamentals, materials, applications and challenges. (16th July 2021) - Ahmed, Aamir; Arya, Sandeep; Gupta, Vinay; Furukawa, Hidemitsu; Khosla, Ajit
Abstract: 4D printing refers to single-material or multi-material printing of a device or object that can be transformed from a 1D strand into pre-programed 3D shape, from a 2D surface into preprogramed 3D shape and is capable of morphing between different dimensions. Such transformations are facilitated by, e.g., heating, light, or swelling in a liquid, electrochemically and by programming different sensitivity to, e.g., swelling into various parts of the designed geometry. These techniques offer adaptability and dynamic response for structures and systems of all sizes, and promises new possibilities for embedding programmability and simple decision making into non-electronic based materials. Potential applications include; robotics-like behavior without the reliance on complex electro-mechanical-chemical devices as well as adaptive products, garments or mechanisms that respond to user-demands and fluctuating environments. In this paper, we have discussed fundamentals and laws governing 4D printing, materials that are employed in 4D printing along with applications such as soft robotics and challenges that need to be overcome for 4D printing to evolve as a mainstream manufacturing technology. Graphical abstract: Image 1 Highlights: Developments and the applications of 4D printing are reviewed. 4D printed techniques are discussed thoroughly. Advances, challenges and future scope are also discussed.